New methodology to determine the compressibility curve in a RIFT process. (May 2014) - Sorrentino, L; Bellini, C; Gerevini, E
In liquid resin infusion processes, the compression phase and the resin flow are important stages that influence the quality of the obtained parts. In this study, an experimental device is presented to measure thickness and pressure variations in order to obtain an experimental compressibility curve that can be implemented in a software dedicated to numerical simulations. To perform these experiments no typical compression testing machine is required and there is no test fluid. The aim of this work is to present a new methodology in order to obtain an empirical relation to determine the compressibility as a power law function. In order to evaluate the reliability of the proposed methodology, the obtained experimental curve is compared with another curve achieved performing standard compaction test.